Possibility of conducting Ijma` in the contemporary world - Amanullah, Muhammad (Serials Publications, 2010)

(untitled)
Classical Muslim jurists unanimously have provided rulings for many pre-modern religious and mundane issues of Muslims in the past. However, many other classical issues have not been solved this way. Rather, different opinions of different schools of law regarding them have continued until today. On the other hand, different types of new human problems and issues emerge everyday from the onset of modern times. Since Islam is considered to be a complete and continuing code of life, it should be able to provide solutions and rulings for these new issues. Likewise, in order to maintain harmony and unity of the society, there should be some continuous ways to reduce differences among Muslim jurists. Among others, ijma` (consensus) is deemed to be a source of law and way to remove such disagreements and to deduct new rulings for the issues mentioned above. The purpose of this paper is to investigate whether it is possible to conduct ijma` at present times. In order to reach this objective, the researcher would critically discuss the arguments of both opponents and supporters on this possibility using both classical and modern sources. This article would be divided into five sections: a definition of ijma`, opponents’ arguments against conducting ijma` at present, supporters’ arguments for this idea, critical analysis of the arguments, and suggestions for how to conduct an ijma` (consensus) and implement its ruling at present times.